Mechanisms of paroxysmal atrial fibrillation in patients with sick sinus syndrome - S. Yu. Ivanov; N. N. Burova; B. B. Bondarenko (Российский кардиологический журнал)
Atrial ectopic activity and atrial conduction in patients with paroxysmal atrial fibrillation (AF) and sick sinus syndrome (SSS) were investigated. Two groups of individuals with coronary heart disease (CHD) and AF paroxysms were examined: 105 participants with SSS, and 115 people with normal sinus function. According to the paroxysm length, three subgroups inside each group were formed: participants with short AF paroxysms (<30 s), prolonged paroxysms (>30 s), and combined ones. In all patients with short AF paroxysms, ectopic atrial activity was prevalent. People with prolonged AF paroxysms demonstrated decreased intra-atrial conduction and increased left atrium size. In the first group, short AF paroxysms were prevalent, prolonged paroxysms were typical for the second group. Authors suggest that it might be explained by activation of ectopic automatism centers in patients with SSS. According to five-year follow-up results, in SSS, paroxysms transformed into chronic AF significantly less often than in normal sinus function. Therefore, in patients with CHD and SSS, the leading arrhythmogenic mechanism is ectopic generation of atrial impulses, and in individuals with normal sinus function, it is reentry.